Analisis Implementasi Permendikbud Nomor 111 Tahun 2014 Tentang Bimbingan Dan Konseling - Rifqi Muhammad (JURNAL ILMIAH EDUKATIF, 2021)
This paper aims to analyze Permendikbud No. 111 of 2014 concerning Guidance and Counseling in Primary and Secondary Education. The following is an explanation of the results of the analysis: 1) Permendikbud No. 111/2014 wants the Basic Education and Secondary Education patterns to be a single pattern that is implemented nationally. So that there is no more dualistic patterns in the implementation of BK; 2) The mistake of saying that BK teachers are professional educators; 3) Permendikbud No. 111/2014 do not speak SKAKK, so far BK teachers are still using SKAKK and SKAKG, in the future they must have the courage to determine Academic Qualification Standards and Competency of BK teachers; 4) The terms counselee, counseling teacher, and counselor are correct. There is a new term, namely "program component" consisting of basic services, responsive services, specialization services and individual planning, system support; 5) The new term is basic services which accommodate four service areas; 6) The new term is responsive service; 7) System support was originally in the realm of management in Permendikbud No.111 of 2014 in the domain of program components; 8) BK program is not complete, only consisting of annual and semester programs; 9) Specifically for data collection tools, if you want to develop 4 service areas as an independent service, an instrument that accommodates this is necessary; 10) Not yet explained the ideal location of the BK building; 11) It is necessary to rearrange the location of the type of room according to its nature, namely public and secret; and 12) There is no explanation on the standard of equipment in each room.